2022
DOI: 10.1093/eurpub/ckac130.243
|View full text |Cite
|
Sign up to set email alerts
|

Late antenatal care initiation and neonatal outcomes in an ethnically diverse maternal cohort

Abstract: Background Ethnic minority status and maternal socio-economic deprivation are linked to delayed access to health care during pregnancy. The link between late antenatal care initiation and neonatal outcomes in settings with high ethnic diversity and social disadvantage is seldom explored. This study examined associations between late antenatal care initiation (first antenatal appointment >12 weeks gestation) and neonatal outcomes of preterm birth (<37 weeks gestation) and low bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, it was lower than that of a study conducted in 54 low- and middle-income countries, with 69.1% in Central and Southern Asia, 63.5% in Eastern and Southeast Asia, 68.1% in Latin America, and the Caribbean and 54.6% in Northern America and Western Europe [ 123 ]. It was also lower than figures from other studies conducted in South Asia (59.5%) [ 124 ], India (69.3%) [ 125 ], Bangladesh (43.0%) [ 126 ], the United Kingdom (79.2%) [ 127 ], Saudi Arabia (75%) [ 126 ], Vietnam (75.2%) [ 128 ] and Malaysia (71.8%) [ 129 ]. This lower percentage may be attributed to sociodemographic variables or ineffective or inadequate strategies carried out in Africa by the relevant authorities.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, it was lower than that of a study conducted in 54 low- and middle-income countries, with 69.1% in Central and Southern Asia, 63.5% in Eastern and Southeast Asia, 68.1% in Latin America, and the Caribbean and 54.6% in Northern America and Western Europe [ 123 ]. It was also lower than figures from other studies conducted in South Asia (59.5%) [ 124 ], India (69.3%) [ 125 ], Bangladesh (43.0%) [ 126 ], the United Kingdom (79.2%) [ 127 ], Saudi Arabia (75%) [ 126 ], Vietnam (75.2%) [ 128 ] and Malaysia (71.8%) [ 129 ]. This lower percentage may be attributed to sociodemographic variables or ineffective or inadequate strategies carried out in Africa by the relevant authorities.…”
Section: Discussionmentioning
confidence: 56%
“…However, research conducted in low-income areas of southern Asia [ 124 ] and sub-Saharan Africa(SSA) [ 22 ] found that first-trimester ANC contact was linked with a maternal age of 25 years and above. Higher parity was also associated with first-trimester ANC contact, according to research from southern Asia [ 124 ] and the UK [ 127 ]. This disparity might be the result of sociocultural variations.…”
Section: Discussionmentioning
confidence: 99%